Skórna reakcja alergiczna na stymulator rdzenia kręgowego (SCS) – opis przypadku = Allergic cutaneous reactions to spinal cord stimulator (SCS) devices – case report - Woźniak, Kamila; Ratuszek-Sadowska, Dorota; Śniegocki, Maciej (Journal of Education, Health and Sport, 2016)
Woźniak Kamila, Ratuszek-Sadowska Dorota, Śniegocki Maciej. Skórna reakcja alergiczna na stymulator rdzenia kręgowego (SCS) – opis przypadku = Allergic cutaneous reactions to spinal cord stimulator (SCS) devices – case report. Journal of Education, Health and Sport. 2016;6(8):587-594. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.61001 http://ojs.ukw.edu.pl/index.php/johs/article/view/3787 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.08.2016. Revised 08.08.2016. Accepted: 26.08.2016. Skórna reakcja alergiczna na stymulator rdzenia kręgowego (SCS) – opis przypadku Allergic cutaneous reactions to spinal cord stimulator (SCS) devices – case report Kamila Woźniak 1, Dorota Ratuszek-Sadowska2, Maciej Śniegocki1 1. Klinika Neurochirurgii, Neurotraumatologii i Neurochirurgii Dziecięcej, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu 2. Katedra i Klinika Rehabilitacji, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu Streszczenie Dolegliwości bólowe to nieprzyjemne doznania, wywołane poprzez potencjalne bądź występujące uszkodzenie tkanek. Jednym z rodzajów bólu przewlekłego jest ból neuropatyczny. Ból ten jest nieprzyjemnym doznaniem, cechującym się uczuciem palenia, pieczenia oraz mrowienia. Nieleczony ból neuropatyczny może trwać długo, stopniowo nasilać się pogarszając funkcjonowanie pacjentów, prowadząc w ostateczności do inwalidztwa. Techniki neuromodulacji pozwalają na redukcję odczuć bólowych i są są względnie bezpieczne dla pacjentów. Jednak w niewielkim odsetku przypadków klinicznych występuje miejscowy odczyn alergiczny na skórze po wszczepieniu przeciwbólowego stymulatora rdzenia kręgowego (SCS). Autorzy przedstawiają opis przypadku klinicznego pacjentki leczonej operacyjnie w Klinice Neurochirurgii, Neurotraumatologii i Neurochirurgii Dziecięcej Szpitala Uniwersyteckiego nr 1 im. dr A. Jurasza w Bydgoszczy, u której istniała konieczność usunięcia stymulatora SCS z powodu miejscowej, skórnej reakcji alergicznej. Słowa kluczowe: stymulator rdzenia kręgowego, SCS, reakcja alergiczna, ból neuropatyczny. Abstract Pain is an unpleasant sensation caused by potential or existing tissue damage. One type of chronic pain is neuropathic pain. Pain is an unpleasant sensation, marked by a feeling of burning, stinging and tingling. If left untreated, neuropathic pain can last for a long time, gradually increase the worsening functioning of patients, leading ultimately to disability. The techniques enable the reduction in the neuromodulation feel pain and are relatively safe for patients. However, in a small proportion of clinical cases is a local allergic reaction on the skin to spinal cord stimulator (SCS). The authors present a case of clinical patient operating treated in the Department of Neurosurgery, Neurotraumatology and Pediatric Neurosurgery, Dr Antoni Jurasz University Hospital No.1 in Bydgoszcz, which was necessary to remove the SCS because of allergic cutaneous reactions. Key words: spinal cord stimulator, SCS, allergic reactions, neuropathic pain.